2018
DOI: 10.7439/ijbr.v9i3.4678
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and antifungal susceptibility testing of Candida isolates in various clinical samples in a tertiary care hospital in Mumbai

Abstract: Background: Over the last few years fungal infection rates have increased and a change is seen in their epidemiology and antifungal susceptibility pattern. Hence this study was conducted to learn the distribution of Candida species in various samples and their antifungal susceptibility pattern.Material and Methods: A total of 60Candida isolates were included in the study. Identification was done by colony morphology and Gram stain. Speciation was carried out by Germ-tube test, urease test, chlamydoconidia prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Only some showed resistance to azole group, 9% to voriconazole and 5% to fluconazole. In contrast Jangla S M et al 17 found 100% sensitivity to azole group, amphotericin-b, Micafungin, Caspofungin, Flucytosine among all Candida species.…”
Section: Discussionmentioning
confidence: 85%
“…Only some showed resistance to azole group, 9% to voriconazole and 5% to fluconazole. In contrast Jangla S M et al 17 found 100% sensitivity to azole group, amphotericin-b, Micafungin, Caspofungin, Flucytosine among all Candida species.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, infections with NAC and overall resistance to antifungals are on the rise. This makes species identification of Candida very essential to prevent treatment failures (Jangla et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In Chile, the prevalence of C. albicans has changed, with a progressive increase in non-albicans infections where C. parapsilosis was the most frequent species, followed by C. tropicalis and C. glabrata. [12,13] The reasons for this change in epidemiology could be severe immunosuppression, comorbidities, prematurity, prolonged antibiotic therapy, elderly patients, indwelling devices etc.…”
Section: Discussionmentioning
confidence: 99%